Enhanced Electromagnetic Absorption of Polyaniline/Fe₃O₄ Nanocomposites in the X-Band Region: Synthesis, Mechanism, and Performance - Annisa Salsabilla; Andri Hardiansyah; M. Zuhnir Piliang; Krisman H. T. Purba; Andi Setiono; Riri Murniati (Indonesian Journal of Chemical Studies, 2026)
PANI can be used as a promising candidate for radar absorbing material. However, the PANI single-composition structure lacks sufficient loss mechanisms, resulting in limited absorption capabilities. This is because PANI is a non-magnetic material, so its microwave absorption properties mostly contributed to dielectric loss. Fe3O4 is highly attractive for enhancing the magnetic loss and electromagnetic attenuation. Therefore, the combination of Fe3O4 and PANI can improve the impedance matching of the nanocomposites while achieving the demand for lightweight. In this research, PANI/Fe3O4 is prepared via chemical oxidative polymerization. The structure and morphology of nanocomposites are characterized using Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray spectroscopy (FESEM-EDX), X-Ray Diffraction (XRD), and Fourier Transform Infrared spectroscopy (FTIR). The microwave parameters are measured using Vector Network Analyzer (VNA). The maximum reflection loss of PANI/Fe3O4 is up to -21.43 dB at 9.2 GHz with its thickness being 2 mm, and its absorption bandwidths exceeding -10 dB are in the range from 8.1 to 10.8 GHz with its thickness being in the range from 2-5 mm. It provides that PANI/Fe3O4 nanocomposites have a great potential application for radar absorbing material.